Hubungan antara Ekspresi Emosi Keluarga Pasien dengan Kekambuhan Penderita Skizofrenia di RS Dr. Sardjito Yogyakarta - Carla R Marchira, Sumarni P., Lusia P.W (Berita Kedokteran Masyarakat (BKM), 2008)
Background:   Schizophrenia  is considered  as severe mental disorder which  causes  big  burden  in one’s  life. After being hospitalized, schizophrenic patients will  live with  their  family while do  regular visitation  to  the hospital to get medical  treatment  under doctor’s  supervision. Schizophrenic  patient’s care  often  becomes  a burden  for the  family,  either  financially,  physically, and  emotionally. Studies  showed  that many  families  have high  expressed emotion due  to  high  relapse  rate on schizophrenic  patient. Sex difference also affects  course and schizophrenic prognosis. There are  still  limited  data about  these  issues  available  in  the  field  of mental  health.Objective: To  observe  correlation  between  families  expressed  emotion  and  relapse  rate  of  schizophrenia patients at Dr. Sardjito Hospital. We  observed drug  compliance and  activity daily  living of  schizophrenia patients as well.Method: This  study  used  cross  sectional  design. Subjects  were  schizophrenic  patients who were  being treated at Dr Sardjito Hospital  and  their  families. The sample size was 31.  Instruments  used  in  this  study were: Expressed emotion  instrument by Soekarto  (2001), Compliance Scale by  Widiyanto  (2002), and ADL  instrument. Data were  analyzed with Chi-Square  and Pearson Correlation  test. We  performed  linear  regression  test  to determine  the contribution  of expressed  emotion  towards  patient’s  relapse  rate.Result  : Data  collection  showed  that  61.3%  schizophrenic  patient’s  families  had  high  expressed  emotion, meanwhile  74.2%  schizophrenic  patients were  relapse. Chi-Square  test  showed  significant correlation  between patient  family’s expressed emotion and schizophrenic patients  relapse  rate(X2=8,22; p<0,05). Pearson Correlation test  also  showed positive  correlation between  patient  family’s  expressed  emotion  and schizophrenic  patients’ relapse  rate  (C=0,59). We  found  the  r2=24,2%.Conclusion: There  is  a  significant  correlation  between  patient’s  family  expressed  emotion with  patient’s relapse  rate. High  expressed  emotion  of  the  family  has  contribution  on  increasing  schizophrenic  patients’ relapse  rate.Keywords  :  expressed  emotion,  relapse, schizophrenia,  drug  compliance, ADL